Evaluation of two mineral trioxide aggregate compounds as pulp-capping agents in human teeth - Accorinte, M. L. R.; Loguercio, A. D.; Reis, A.; Bauer, J. R. O.; Grande, R. H. M.; Murata, S. S.; Souza, V; Holland, R. (Wiley, 2009)
Aim: The present randomized, controlled prospective study evaluated the histomorphological response of human dental pulps capped with two grey mineral trioxide aggregate (MTA) compounds. Methodology: Pulp exposures were performed on the occlusal floor of 40 human permanent pre-molars. The pulp was capped either with ProRoot (Dentsply) or MTA-Angelus (Angelus) and restored with zinc oxide eugenol cement. After 30 and 60 days, teeth were extracted and processed for histological examination and the effects on the pulp were scored. The data were subjected to Kruskal-Wallis and Conover tests (α = 0.05). Results: In five out of the 40 teeth bacteria were present in pulp tissue. No significant difference was observed between the two materials (P > 0.05) in terms of overall histological features (hard tissue bridge, inflammatory response, giant cells and particles of capping materials). Overall, 94% and 88% of the specimens capped with MTA-Angelus and ProRoot, respectively, showed either total or partial hard tissue bridge formation (P > 0.05). Conclusions: Both commercial materials ProRoot (Dentsply) and MTA-Angelus (Angelus) produced similar responses in the pulp when used for pulp capping in intact, caries-free teeth. © 2009 International Endodontic Journal.
Keywords: Hard tissue bridge; Inflammatory response; Mineral trioxide aggregate; Pulp-capping human teeth; aluminum derivative; calcium derivative; mineral trioxide aggregate; oxide; silicate; tooth cement; zinc oxide eugenol; adult; clinical trial; comparative study; controlled clinical trial; controlled study; dentin sensitivity; drug combination; drug effect; endodontics; follow up; giant cell; human; microbiology; odontoblast; pathology; prospective study; pulpitis; randomized controlled trial; single blind procedure; tooth pulp; tooth pulp disease; Adult; Aluminum Compounds; Calcium Compounds; Dental Cements; Dental Pulp; Dental Pulp Capping; Dental Pulp Exposure; Dental Pulp Necrosis; Dentin Sensitivity; Dentin, Secondary; Drug Combinations; Follow-Up Studies; Giant Cells; Humans; Odontoblasts; Oxides; Prospective Studies; Pulpitis; Silicates; Single-Blind Method; Zinc Oxide-Eugenol Cement